Virtual Tourism Business Networks in Developing Countries - Barradas, Luís Cláudio (2012)
Since the rising of Computer and Information Technologies, that enterprises and organizations explore them to run their businesses, in order to explore new business opportunities, increase profits and decrease costs. Due several reasons, most of micro, small and medium enterprises located in remote communities, especially those located in developing countries, face a number of obstacles and difficulties due to their business structure and limited access to information and communication infrastructures. This paper presents the conclusive remarks of a master thesis that aims the development of a model for a virtual business network, bringing together tourism industry players located in remote communities, in order to provide them the opportunity to, at a low cost, join to the information society, explore new business opportunities and acquire global visibility. This virtual business network is fostered and relies on a JXTA P2P distributed e-marketplace model that seems to be an effective and alternative way to overtake the presented problem.